Interdigitated Deletion Complexes on Mouse Chromosome 5 Induced by Irradiation of Embryonic Stem Cells - Schimenti, John C.; Libby, Brian J.; Bergstrom, Rebecca A.; Wilson, Lawriston A.; Naf, Dieter; Tarantino, Lisa M.; Alavizadeh, Alireza; Lengeling, Andreas; Bucan, Maja

(untitled) (Genome Research, 2000)
Chromosome deletions have several applications in the genetic analysis of complex organisms. They can be used as reagents in region-directed mutagenesis, for mapping of simple or complex traits, or to identify biological consequences of segmental haploidy, the latter being relevant to human contiguous gene syndromes and imprinting. We have generated three deletion complexes in ES (Embryonic Stem) cells that collectively span ∼ 40 cM of proximal mouse chromosome 5. The deletion complexes were produced by irradiation of F1 hybrid ES cells containing herpes simplex virus thymidine kinase genes (tk) integrated at the Dpp6, Hdh (Huntington disease locus), or Gabrb1 loci, followed by selection for tk-deficient clones. Deletions centered at the adjacent Hdh and Dpp6 loci ranged up to ∼ 20 cM or more in length and overlapped in an interdigitated fashion. However, the interval between Hdh and Gabrb1 appeared to contain a locus haploinsufficient for ES cell viability, thereby preventing deletions of either complex from overlapping. In some cases, the deletions resolved the order of markers that were previously genetically inseparable. A subset of the ES cell–bearing deletions was injected into blastocysts to generate germline chimeras and establish lines of mice segregating the deletion chromosomes. At least 11 of the 26 lines injected were capable of producing germline chimeras. In general, those that failed to undergo germline transmission bore deletions larger than the germline-competent clones, suggesting that certain regions of chromosome 5 contain haploinsufficient developmental genes, and/or that overall embryonic viability is cumulatively decreased as more genes are rendered hemizygous. Mice bearing deletions presumably spanning the semidominant hammertoe locus (Hm) had no phenotype, suggesting that the classic allele is a dominant, gain-of-function mutation. Overlapping deletion complexes generated in the fashion described in this report will be useful as multipurpose genetic tools and in systematic functional mapping of the mouse genome.